The Financial Crisis and Its Impacts on Global Agriculture - Lin, Justin Yifu; Martin, Will (2012)
The financial crisis arose in the industrial countries, but has affected developing countries through higher interest rates, sharp changes in commodity prices, and reductions in investment, trade, migration and remittances. For most low-income countries, shocks that affect food prices or wage rates for unskilled workers seem likely to have the largest impact on poverty, with the declines in key food prices associated with the crisis helping to reduce poverty, while declining trade, investment, and remittance flows have had adverse impacts on the poor. Policies to address the crisis must include measures to deal with financial sector problems, the resulting reductions in aggregate demand, and the particular vulnerabilities of poor people. Given the complexity of the impacts from financial crises and commodity price shocks, there is a strong case for developing better social safety net policies that can offset the adverse impacts of a wide range of different shocks on poor people without creating costly market distortions.